Formação de jovens leitores em bibliotecas públicas: aspectos sociais e subjetivos de práticas e escolhas de leituras literárias - Daniela Chaves Correa de Figueiredo (2015)
It is not unusual to hear nowadays in various contexts of our society that youth does not read. However, in readers formation experiments in public libraries, we note the presence of young people borrowing books or participating in book clubs. Therefore, based on researches on literary literacy, and according to the concept of readers that, belonging to different reading communities, produce and negotiate meanings in a dialogic interaction with texts, this study seeks to understand subjective and socio-cultural aspects of young readers practices and choices of literary readings in four municipal public libraries in Belo Horizonte, discussing limits and contributions of this context in their formation as readers. In order to do that, we have interviewed 27 young readers of literature who attend these institutions, observed the reading activities promoted there, the daily lives of these libraries and analyzed their cultural activities programs. As a result it was possible to state that: a) the family is the main forum to encourage literary reading; b) the dialogical perspective contributes to the engagement in reading practices; c) identification with narrative and its characters favors the approach to literary texts; d) the subjective textual choices collaborate to the socio-cultural exercise of this practice; e) public libraries are meeting places that bring young people close to books, promoting their education as readers.